Estimación del tipo de cambio real multilateral de equilibrio para la Argentina mediante modelos uniecuacionales, 1970-2001 - Lanteri, Luis (2002)
This  paper uses a  one-equation model proposed by Baífes, Elbadawi and O'Connell (1999) with the intention of  measuring the  degree  of  misalignment between the  observed  multilateral real  exchange and  its  estimated  level of  long run  equilibrium, in the Argentinean case. With that purpose, annual data covering the period 1970-2001 for the multilateral real exchange rate and other macroeconomic variables  are  used. The econometric model used is a  methodology alternative to  most recent estimatio- ns that use vector error correction (VEC) models, in a tradition established by Johansen (1988). Our estimations show  that  by the  end  of the  year  2001 the Argentinean currency was overvalued between 30% and 45% with respect to its equilibrium multilateral real  exchange rate, depending  on  whether  we use wholesale or consumer prices as the numerator of the multilateral real exchange rate.